Wild cats : past & present - Becker, John E., 1942-; Hallett, Mark, 1947- (Plain City, OH : Darby Creek, 2008)
Photographs and text profile the different types of wild cats found around the world, with information on their physical characteristics, distribution, behavior, and whether or not they are endangered.
Includes bibliographical references (p. 76-78) and index.
6.6
5-8
Keywords: Felidae -- Juvenile literature; Cat family (Mammals); Wild cats